Field programmable gate array based moving object tracking system for robot navigation - Hoang T. Tran; Dong LT. Tran; Quang N. Pham; Thanh C. Vo; Quan NA. Nguyen; Thang K. Nguyen; Duyen M. Ha; Minh T. Nguyen (Bulletin of Electrical Engineering and Informatics, 2023)
This paper proposes a method in which an object tracking robot system is implemented on field programmable gate arrays (FPGAs). The OV7670 camera provides real-time object pictures to the system. To improve picture quality, images are put via the median filter phase. The item is distinguished from the backdrop based on color (red), after which it is subjected to a mathematical morphological approach of filtering to eliminate noise. To send the robot control signals, the object's (new) coordinates are found. In this method, the median filter, color separation, hardware IP cores, and morphological filter are all part of the embedded system on FPGA. Through the direct memory access (DMA) controller, these cores may communicate and perform high-speed pipeline computing at higher data rates. The entire system is executed in real-time on Xilinx's spartan-6 FPGA KIT. The results show practical and promise.